T-cell bispecific antibodies in node-positive breast cancer: novel therapeutic avenue for MHC class I loss variants. (29th March 2019) - Messaoudene, M; Mourikis, T P; Michels, J; Fu, Y; Bonvalet, M; Lacroix-Trikki, M; Routy, B; Fluckiger, A; Rusakiewicz, S; Roberti, M P; Cotteret, S; Flament, C; et al.
Abstract: Background: Tumor-infiltrating lymphocytes (TILs) represent a prognostic factor for survival in primary breast cancer (BC). Nonetheless, neoepitope load and TILs cytolytic activity are modest in BC, compromising the efficacy of immune-activating antibodies, which do not yet compete against immunogenic chemotherapy. Patients and methods: We analyzed by functional flow cytometry the immune dynamics of primary and metastatic axillary nodes [metastatic lymph nodes (mLN)] in early BC (EBC) after exposure to T-cell bispecific antibodies (TCB) bridging CD3ε and human epidermal growth factor receptor 2 (HER2) or Carcinoembryonic Antigen-Related Cell Adhesion Molecule 5 (CEACAM5), before and after chemotherapy. Human leukocyte antigen (HLA) class I loss was assessed by whole exome sequencing and immunohistochemistry. One hundred primary BC, 64 surrounding 'healthy tissue' and 24 mLN-related parameters were analyzed. Results: HLA loss of heterozygosity was observed in EBC, at a clonal and subclonal level and was associated with regulatory T cells and T-cell immunoglobulin and mucin-domain-3 expression restraining the immuno-stimulatory effects of neoadjuvant chemotherapy. TCB bridging CD3ε and HER2 or CEACAM5 could bypass major histocompatibility complex (MHC) class I loss, partially rescuing T-cell functions in mLN. Conclusion: TCB should be developed in BC to circumvent low MHC/peptide complexes.